Influence of housing and season on pubertal development, boar taint compounds and skin lesions of male pigs. (19th September 2013) - Prunier, A.; Brillouët, A.; Merlot, E.; Meunier-Salaün, M. C.; Tallet, C.
Abstract : Rearing entire pigs may lead to meat quality and welfare problems in relation to pubertal development. A better knowledge of the sources of variation of pubertal development, behaviour and boar taint is needed before generalizing entire male pigs. From 84 days of age, entire male pigs were reared in groups of 10 either in a conventional (C, 1 m²/animal, slatted floor) or an enriched (E, 2.5 m²/animal, straw bedding, outdoor run) housing during spring or autumn and fed ad libitum ( n =10/housing/season). Mounting behaviour was observed for 3 h during the third (M3), fourth (M4) and fifth (M5) months of age. The total number of skin lesions was counted on both sides of the pigs 1 day before the behavioural recordings. The time spent in the outdoor run was also recorded during 3 days per month. The animals were slaughtered at 161±1 days of age (122±9 kg live weight). Blood samples were collected at 89 (M3), 119 (M4) and 152 (M5) days of age and at slaughter for the testosterone and oestradiol measurements. The testes were collected at slaughter, freed from the surrounding tissues and weighed. The fat samples were collected for the androstenone and skatole concentration measurement. Plasma testosterone and oestradiol-17 β (oestradiol), fat androstenone and skatole and weight of the testes did not differ between the housing systems. Plasma testosterone (8.3 v. 3.9 nmol/l, P <0.05) and oestradiol (12.0 v. 9.2 pmol/l, P <0.1) at M3, fat skatole (0.124 v. 0.043, P <0.03) and weight of the testes (587 v. 512 g, P <0.05) were higher in the autumn than in the spring trial, suggesting that the pubertal development was accelerated. The number of received mounting behaviours was slightly higher in the autumn ( P =0.08) trial and was markedly higher in the E than in the C environment ( P <0.003). Skin lesions were more numerous in the C than in the E housing at M4 and M5 and in the spring than in the autumn trial at M3 and M4 ( P <0.05). Fat androstenone and the number of performed mounting behaviours were significantly correlated between each other and with numerous indicators of the pubertal development ( P <0.05). The number of skin lesions was correlated with plasma testosterone and live weight ( P <0.05). Overall, this study suggests the effect of season on sexual development, the effect of the housing system on behaviour, and demonstrates the links between sexual hormones, behaviour and boar taint.